SAT0582-HPR Occupational Characterization and Relation between Working Condition and Disease Activity or Functionality in Patients with Rheumatoid Arthritis. (23rd January 2014) - Beltran, D.; Urbina, A.; Sandoval, C.; Villarreal, L.; Real, A. P.; Boon, P.; Palomino, A.; Santos-Moreno, P.
Abstract : Background: Rheumatoid arthritis (RA) is a disease that in most cases is associated with disability and loss of earning capacity. There is a lack of information about occupation of rheumatoid arthritis patients in Colombia, being this field important in order to improve clinical and social outcomes for them. On the other hand, there are no data about the relationship between working or not-working condition with RA activity and functional status, being this information relevant for implementation of social programs for this population. Objectives: The aim of this study was to describe the occupation in a cohort of RA patients and to describe functionality and disease activity and it`s possible relationship with working or retirement condition in a cohort of RA patients in a specialized center in Colombia. Methods: A descriptive cross sectional study was realized. A revision of medical records of a cohort of RA patients was performed, including occupational therapy records. Each patient was evaluated for DAS28, HAQ and OPHI2 (Occupational Performance History Interview 2). Patients were classified in two categories: working and retirement condition, last one was divided into: retirement because of age and retirement for disability. Descriptive epidemiology was done, percentages and averages were calculated; and Pearson´s statistics was used for by-variated analysis. Results: Of the 177 RA patients included, 147 (83.1%) were women and 30 (16.9%) were men. Mean age 59.6 y/o, for women 58.6 and for men 60.6. Average DAS 28 for all patients 2.73 (2.85 for women and 2.62 for men), average HAQ were 0.29 (0.33 for women and 0.25 for men). Retired workers were 77.9% and active workers 22.1%. Administrative workers were 34 (19.2%), house keepers were 34 (19.2%), high impact workers (machine operators, sewing operators and others) were 25 (14.1%), low impact workers (maid services, health workers and others) were 78 (44.1%), no well-defined condition were 6 (3.4%). Regarding DAS28 and HAQ in average for administrative workers were 3.0 and 0.25, for house keepers were 2.44 and 0.29, for high impact workers were 2.81 and 0.41, for low impact workers were 2.97 and 0.34. It was established correlation between occupation and disease activity (p < 0.0099), but not with functionality. Conclusions: Interestingly most active RA patients were administrative workers, followed by low impact workers. In general for all types of occupations HAQ scores were low. Study suggests working patients had more active disease (average moderate activity) compared to retired patients (mild activity), but they had better functionality than retired patients. Disclosure of Interest: None Declared